Frequency And Significance of Electrocardiographic Changes in Beta Thalassemia Major Patients - Hamid, Naila; Shafique, Muhammad Faisal; Zaman, Qamar -uz-; Niaz, Hafsa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the electrocardiographic changes among beta thalassemia major patients as the marker of cardiac complications at later stages of life.Study Design: Prospective observational study.Place and Duration of Study: Department of Pediatrics and Neonatology, Pak Emirates Military Hospital Rawalpindi from Jul 2018 to Dec 2018.Methodology: One hundred and thirty patients of age 5-20 years with beta thalassemia major were included in the study. Patients were attending the thalassemia centre regularly.Results: Out of total 130 patients, 70 (53.84%) were males and 60 (46.15%) were females. Out of 81 (56.92%) patients showed at least one electrocardiographic change while 49 (37.69%) patients showed normal electrocardiography. Remarkable electrocardiographic changes were sinus tachycardia, arrhythmias, T-wave inversions, long QTc interval and sinus bradycardia. There was statistically significant association in the increased serum ferritin levels, electrocardiographic changes, number of blood transfusions and occurrence of ECG changes (p